3D-printed PLA/PEO blend as biodegradable substrate coating with CoCl2 for colorimetric humidity detection. (June 2022) - Chaiya, Nattanicha; Daranarong, Donraporn; Worajittiphon, Patnarin; Somsunan, Runglawan; Meepowpan, Puttinan; Tuantranont, Adisorn; Rakbamrung, Nawasit; Topham, Paul D.; Tighe, Brian J.; Mahomed, Anisa; Punyodom, Winita
Abstract: This study aimed to fabricate biodegradable substrate with colorimetric humidity indicator for detective moisture in food packaging. The poor properties of poly(lactic acid) (PLA) were enhanced by melt blending PLA with non-toxic poly(ethylene oxide) PEO at 180 °C. Specifically, three-dimensional (3D) substrates of PLA/PEO blends were fabricated by solvent-cast 3D printing. Furthermore, cobalt chloride (CoCl2 ) solution was printed onto the substrate with an inkjet printer to serve as a colorimetric humidity sensing indicator. It found that the flexibility and thermal stability of the PLA were improved and the hydrophilicity was increased with an increase in PEO content. Color changes and the sensitivity of this material were confirmed using image analysis and total color difference. The CoCl2 indicator displayed color changes that ranged from blue to pink under ambient conditions (above 60%RH), revealing suitable potential for frozen food packaging material with aim to detect amount of moisture in the packaging. Graphical Abstract: ga1 Highlights: PLA/PEO blends as environmental friendly materials were investigated for colorimetric humidity detective label. The novel biodegradable 3D substrate of PLA/PEO blends was successfully prepared by solvent-casting 3D printing method. The addition of PEO in PLA matrix lead to a biodegradable substrate of higher flexibility and hydrophilicity. This designed label showed moisture sensing ability along with an accuracy and clearly noticeable color change. This study provides a low-cost, simple, controllable, and fast way to design and fabricate colorimetric humidity label.